External quality assessment study for ebolavirus PCR-diagnostic promotes international preparedness during the 2014 - 2016 Ebola outbreak in West Africa. - Heinz Ellerbrok; Sonja Jacobsen; Pranav Patel; Toni Rieger; Markus Eickmann; Stephan Becker; Stephan Günther; Dhamari Naidoo; Livia Schrick; Kathrin Keeren; Angelina Targosz; Anette Teichmann; et al. (PLoS Neglected Tropical Diseases)
During the recent Ebola outbreak in West Africa several international mobile laboratories were deployed to the mainly affected countries Guinea, Sierra Leone and Liberia to provide ebolavirus diagnostic capacity. Additionally, imported cases and small outbreaks in other countries required global preparedness for Ebola diagnostics. Detection of viral RNA by reverse transcription polymerase chain reaction has proven effective for diagnosis of ebolavirus disease and several assays are available. However, reliability of these assays is largely unknown and requires serious evaluation. Therefore, a proficiency test panel of 11 samples was generated and distributed on a global scale. Panels were analyzed by 83 expert laboratories and 106 data sets were returned. From these 78 results were rated optimal and 3 acceptable, 25 indicated need for improvement. While performance of the laboratories deployed to West Africa was superior to the overall performance there was no significant difference between the different assays applied.